Evaluation of The Immigration Assistance Program: Based on The Cipp Model in Lombang Village, Indramayu Regency - Meryance Natalia Panggabean; Maria Puspitasari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The government has undertaken various efforts to prevent and minimize opportunities for human trafficking, including community empowerment initiatives. One form of empowerment is implemented by the Directorate General of Immigration through the Immigration Assisted Village (Desa Binaan Imigrasi/DBI) program. This commendable initiative requires supporting efforts through program evaluation, which became the objective of this study. The research was conducted in Lombang Village, Indramayu Regency, using the evaluation concept introduced by Daniel Leroy Stufflebeam, namely CIPP (Context, Input, Process, Product). A qualitative approach was employed, with research informants consisting of program recipient communities and implementing officers. The study was supported by secondary data in the form of program reports and relevant regulations. The findings reveal that the program has been operational for one year. In terms of the Input aspect, it was evident that human resources were inadequate in both quantity and expertise, accompanied by a limited budget, which hampered program continuity. Regarding the Process aspect, community participation was insufficiently accommodated, and the limited input negatively affected the program’s overall implementation. Overall, the program’s execution, which demonstrated weaknesses in the Input, Process, and Product aspects, resulted in a limited reach of the target population and low public awareness.